Qualitative exploration of intentions, concerns and information needs of vaccine‐hesitant adults initially prioritised to receive COVID‐19 vaccines in Australia - Jessica Kaufman; Kathleen L. Bagot; Jane Tuckerman; Ruby Biezen; Jane Oliver; Carol Jos; Darren Suryawijaya Ong; Jo‐Anne Manski‐Nankervis; Holly Seale; Lena Sanci; Jane Munro; J. Simon Bell; et al. (Elsevier, 2022)
Abstract Objective: Tailored communication is necessary to address COVID‐19 vaccine hesitancy and increase uptake. We aimed to understand the information needs, perceived benefits and barriers to COVID‐19 vaccination of people prioritised, but hesitant to receive the vaccine. Method: In this qualitative study in Victoria, Australia (February‐May 2021), we purposively sampled hesitant adults who were health or aged/disability care workers (n=20), or adults aged 18‐69 with comorbidities or aged ≥70 years ('prioritised adults'; n=19). We thematically analysed interviews inductively, then deductively organised themes within the World Health Organization Behavioural and Social Drivers of vaccination model. Two stakeholder workshops (n=12) explored understanding and preferences for communicating risks and benefits. We subsequently formed communication recommendations. Results: Prioritised adults and health and aged care workers had short‐ and long‐term safety concerns specific to personal circumstances, and felt like "guinea pigs". They saw vaccination as beneficial for individual and community protection and travel. Some health and aged care workers felt insufficiently informed to recommend vaccines, or viewed this as outside their scope of practice. Workshop participants requested interactive materials and transparency from spokespeople about uncertainty. Conclusions and public health implications: Eleven recommendations address communication content, delivery and context to increase uptake and acceptance of COVID‐19 vaccines.